2016
DOI: 10.4103/0301-4738.195594
|View full text |Cite
|
Sign up to set email alerts
|

Results and safety profile of trainee cataract surgeons in a community setting in East Africa

Abstract: Purpose:To evaluate the results and safety profile of assistant medical officer ophthalmologists (AMO-O) performing cataract surgery in the last stage of their surgical training, before their appointment to local communities.Methods:We retrospectively analyzed the records of patients who underwent cataract surgery by AMO-Os at Dar es Salaam, Comprehensive Community Based Rehabilitation for Tanzania Disability Hospital between September 2008 and June 2011. Surgical options were either extracapsular cataract ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…This was slightly higher than other studies from India and Nepal [15][16][17][18] but less than most studies from Africa. [23][24][25] Mavrakanas et al reported an overall complication rate of 8.2% with less in MSICS surgeries (5.3%) as compared to ECCE (10.2%). [23] However, these surgeries were carried out by cataract surgeons undergoing training.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations
“…This was slightly higher than other studies from India and Nepal [15][16][17][18] but less than most studies from Africa. [23][24][25] Mavrakanas et al reported an overall complication rate of 8.2% with less in MSICS surgeries (5.3%) as compared to ECCE (10.2%). [23] However, these surgeries were carried out by cataract surgeons undergoing training.…”
Section: Plos Onementioning
confidence: 99%
“…[23][24][25] Mavrakanas et al reported an overall complication rate of 8.2% with less in MSICS surgeries (5.3%) as compared to ECCE (10.2%). [23] However, these surgeries were carried out by cataract surgeons undergoing training. [23] Complication rate was also much lower than what was reported on PRECOG and other studies.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations